2020
DOI: 10.5713/ajas.19.0393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Antrodia cinnamomea fermented product supplementation on metabolism pathways of antioxidant, inflammatory, and lipid metabolism pathways-a potential crosstalk

Abstract: Objective: This study was conducted to fathom the underlying mechanisms of nutrition intervention and redox sensitive transcription factors regulated by Antrodia cinnamomea fermented product (FAC) dietary supplementation in broiler chickens.Methods: Four hundreds d-old broilers (41±0.5 g/bird) assigned to 5 groups were examined after consuming control diet, or control diet replaced with 5% wheat bran (WB), 10% WB, 5% FAC, and 10% FAC. Liver mRNA expression of antioxidant, inflammatory and lipid metabolism path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…G. lucidum has been claimed to dampen the progression of inflammatory breast cancer by downregulating the expression of Nf-κB ( Martinez-Montemayor et al., 2008 ; Suarez-Arroyo et al, 2013 ). Lee et al. (2020b) also reported the effects of A. cinnamomea –fermented powder in downregulating the liver expression of genes involving inflammatory pathways such as NF-κB , iNOS , TNF-α , IL-1β , NLRP3, and COX2 in broiler chickens receiving high-NSP diets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…G. lucidum has been claimed to dampen the progression of inflammatory breast cancer by downregulating the expression of Nf-κB ( Martinez-Montemayor et al., 2008 ; Suarez-Arroyo et al, 2013 ). Lee et al. (2020b) also reported the effects of A. cinnamomea –fermented powder in downregulating the liver expression of genes involving inflammatory pathways such as NF-κB , iNOS , TNF-α , IL-1β , NLRP3, and COX2 in broiler chickens receiving high-NSP diets.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies had reported the application of SSF using filamentous fungi on agricultural byproducts which further exerted positive effects on monogastric animals. Lee et al., 2020a , Lee et al., 2020b used Antrodia cinnamomea on the SSF of WB and produced bioactive compounds such as phenolic compounds, polysaccharides, and triterpenoids, which exerted growth promoting, antioxidant, and anti-inflammation effects in broilers, which suggest the potential of SSF on the utilization of agroprocessing byproducts to produce bioactive compounds and functional feedstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic compounds derived from fungus have been reported to activate the Nrf2-Keap1 pathway in a suppressed Nrf2 diabetic rat model [ 34 ]. Furthermore, A. cinnamomea , a brown-rot fungus that exerted medicinal effects similar to those of L. sulphureus , reported the enhanced expression of Nrf2 , HO-1 , and SOD mRNAs in the liver of 35-day-old chickens fed upon its fermented feedstuff, as well as a further increase in SOD activity in the serum [ 11 , 15 ]. Therefore, it can be validated that FL, as a medicinal fungus fermented products, may have also improved the antioxidative status of broilers via a similar mechanism as reported by above mentioned previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…WB, a solid-state that is fermented by the Trichoderma sp., has been shown to exhibit antioxidant properties and to improve the nutrition value of WB, which could potentially be a low-cost feedstuff candidate [ 13 , 14 ]. Solid-state WB fermented by Antrodia cinnamomea was found to be suitable for producing bioactive compounds, such as phenolics, triterpenoids, and polysaccharides, as well as for growth promotion and its antioxidative and anti-inflammatory effects in broiler feeding trials [ 11 , 15 ]. According to these studies, the use of fungal SSF in agricultural by-products is viable for producing functional feedstuffs that contain bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that PTGER2 has potential in producing anti-inflammatory cytokines including IL-10 in vivo ( Okla et al., 2019 , Tomić et al., 2019 ). IL-10/Cox2/PTGER2 could be influenced by Mycobacterium avium infection in dendritic cells and by Antrodia cinnamomea fermented product in chicken cells ( Kim et al., 2019 , Lee et al., 2019 ). In addition, interaction of mesenchymal stem cells, S. typhimurium , and L. acidophilus increased Cox2, IL-6, IL-8, and PTGER2 ( Kol et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%